A Low-Noise Amplifier Design Using the Performance Limitations of a Microwave Transistor for the Ultra-Wideband Applications - Gunes, Filiz; Demirel, Salih; Ozkaya, Ufuk (WILEY, 2010)
In this work, a design method of an ultra-wideband, low-noise amplifier (LNA) is put forward exploiting the performance limitations of a single high-quality discrete transistor. For this purpose. the compatible (noise F, input VSWR lib gain GT) triplets and their (Zs, ZI,) terminations of the microwave transistor are used for the feasible design target space with the minimum noise F (I), maximum gain GT, (f), and a low constant input VSWR Vireq using the optimum noise impedance Z,(f), and the maximum gain termination Zimia.(f) over the available. bandwidth B. In the next stage, this multiobjective design process is reduced to the Darlington synthesis of the corresponding Z,(/), Z.,,, s(f) terminations using the unit elements and short-circuited stubs in the T-, L-, 11-configurations. This synthesis is transformed to an optimization process with the determined feasible target space and optimization variables. Here, particle swarm intelligence is successfully implemented as a comparatively simple and efficient optimization tool in both verification of the design target space and the design process of the input and output matching circuits. Typical design examples are given with their challenging performances in the simple matching configurations realizable by the microstrip line technology. Furthermore, the performances of the synthesized amplifiers are compared using an analysis programme in mATLAB code and a microwave system simulator and verified to agree with each other and the design target space. (C) 2010 Wiley Periodicals, Inc Int J RF and Microwave CAE 20 535 545. 2010
Keywords: transducer gain; noise figure; input VSWR; input/output impedance; stability, unit element; short-circuited stub; feasible design target space; feasible design variable space; optimization; DATA SHEETS; Computer Science; Engineering